2023
DOI: 10.3390/biomedicines11051502
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Diabetic Nephropathy and Development of Diabetic Macular Edema in Addition to Diabetic Retinopathy

Abstract: This study aimed to examine the relationship between diabetic retinopathy (DR) and systemic factors. We evaluated 261 patients (143 men, 118 women, aged 70.1 ± 10.1 years) with type 2 diabetes. All participants underwent a fundus examination, fundus photography using spectral domain optical coherence tomography (SD-OCT), and blood tests. For glycated hemoglobin (HbA1c) levels, the average and highest values in the past were used. We observed DR in 127 (70 men and 57 women) of 261 patients. Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…However, as the anti-VEGF drug is metabolized in the eye, macular edema reappears when the intraocular concentration of the anti-VEGF drug is lower than the therapeutic concentration, so the anti-VEGF drug needs to be injected repeatedly. The anti-VEGF drug, 3 + PRN is widely recognized and used in clinical practice and its effectiveness and safety have been confirmed by several previous studies [14,15]. With the deepening of clinical research, the latest view is that early intensification of anti-VEGF drugs is more effective for edema resolution and visual protection.…”
Section: Discussionmentioning
confidence: 88%
“…However, as the anti-VEGF drug is metabolized in the eye, macular edema reappears when the intraocular concentration of the anti-VEGF drug is lower than the therapeutic concentration, so the anti-VEGF drug needs to be injected repeatedly. The anti-VEGF drug, 3 + PRN is widely recognized and used in clinical practice and its effectiveness and safety have been confirmed by several previous studies [14,15]. With the deepening of clinical research, the latest view is that early intensification of anti-VEGF drugs is more effective for edema resolution and visual protection.…”
Section: Discussionmentioning
confidence: 88%
“…Beyond the influence of the course and severity of diabetes on DME, the systemic influence caused by DN and its promoting effect on DME should also be considered. Previous studies reported that albuminuria, eGFR and DN grade were correlated with DME [9][10][11][12] . In addition, without specific eye treatment for DME, hemodialysis could significantly decrease the central retinal thickness and increase the BCVA [13][14] .…”
Section: Discussionmentioning
confidence: 92%
“…Although epidemiological research has shown that the incidence of DME in diabetes patients is approximately 5.5% [22] , that in DR patients reaches 21.1% [23] , and that in patients with proliferative DR (PDR) is as high as 66.2% [24] . Since the severity of DN is positively correlated with the severity of DME and DR [25] , theoretically, the incidence of DME is greater in patients with DN and PDR.…”
Section: Discussionmentioning
confidence: 99%